Dirty bosons in a three-dimensional harmonic trap. (28th September 2017) - Khellil, Tama; Pelster, Axel
Abstract: We study a three-dimensional Bose–Einstein condensate in an isotropic harmonic trapping potential with an additional delta-correlated disorder potential and investigate the emergence of a Bose-glass phase for increasing disorder strength. At zero temperature a first-order quantum phase transition from the superfluid phase to the Bose-glass phase is detected at a critical disorder strength, which agrees with the findings in the literature. Afterwards, we study the interplay between temperature and disorder fluctuations on the respective components of the particle density. In particular, we find for smaller disorder strengths that a superfluid region, a Bose-glass region, and a thermal region coexist. Furthermore, depending on the respective system parameters, three phase transitions are detected, namely, one from the superfluid to the Bose-glass phase, another one from the Bose-glass to the thermal phase, and finally one from the superfluid to the thermal phase. All these results are obtained by extending a quite recent Hartree–Fock mean-field theory for the dirty boson problem, which is based on the replica method, from the homogeneous case to a harmonic confinement.